Roles of RNA modifications in aging and age-related diseases - Eunseok Kang; Rosa Haque; Hanseul Lee; Seung-jae V. Lee (BMB reports, 2025)
RNA modifications are key epigenetic alterations that play regulatory functions in RNA biology, including RNA stability and translation. Emerging evidence indicates that RNA modification is crucial for various physiological and pathological processes, including aging. This review describes functions of key RNA modifications, including N 6 -methyladenosine (m 6 A), 5-methylcytosine (m 5 C), N 7 -methylguanosine (m 7 G), 2’-O-methylation (Nm), N 1 -methyladenosine (m 1 A), adenosine-to-inosine (A-to-I) RNA editing, pseudouridylation (ψ), and N4-acetylcytidine (ac4C), highlighting their roles in aging and age-associated diseases. We also discuss dynamics of RNA modifications and associated protein factors during aging. This review provides important information on molecular mechanisms underlying aging regulation, focusing on effects of RNA modifications, which can help us understand healthy longevity in humans. [BMB Reports 2025; 58(9): 389-396]